Pelanggaran Prinsip-Prinsip Etika Bisnis Islam dalam Kasus Korupsi Pengoplosan Pertamax oleh PT. Pertamina - Dewi, Melati Sukma Dewi (Fakultas Ekonomi dan Bisnis Islam IIQ An Nur Yogyakarta, 2025)
Ethics are the main foundation in carrying out sustainable and responsible business activities, especially from an Islamic perspective which emphasizes moral and spiritual values. This study aims to identify and analyze the violations of Islamic business ethics principles within the Pertamina Pertamax blending corruption case. Employing a qualitative case study method, the research analyzes secondary data including media reports, investigative findings, and relevant documents. The results indicate that the Pertamax adulteration practices transgressed the principles of honesty (shidq), trustworthiness (amanah), justice ('adl), responsibility (mas'uliyyah), and the prohibition of harmful practices (dharar). These violations suggest weaknesses in internal oversight and the implementation of corporate ethical values. The conclusion of this study underscores the necessity of strengthening corporate governance based on Islamic business ethics to prevent similar cases and restore public trust in state-owned enterprises.